PROSPEK BUDIDAYA KENTANG HITAM (Coleus tuberosum) DI LAHAN KEKERINGAN - Yudi Rinanto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract - The utilization of Coleus tuberosus Benth is not common for Indonesian citizen especially for the carbohydrate sources. Whereas, the Black Potatoes have a great potention to be develop at dryland . Dryland is distribute rife in Indonesia. Unfortunately, the utilization is not optimal exploitation. The adaptability of the black potatoes in dryland is very well. It can be seen from the requirement to grow plants that spread in many kind of land from low land until high land variety. Black potatoes can be used as carbohydrate source because the content of protein  higher than potatoes commonly in highland comercial . In addition, more black potatoes resistant to the diseases. The cultivation of black potatoes  easier than the commercial potato crops. By those reason, The utilization black potatoes have a good prospective in Indoneasia especially in dry land. Keywords: Coleus tuberosus, dry land